A case for microbial therapeutics to bolster colony health and performance of honey bees - Killam, Sophie M.; Daisley, Brendan A.; Kleiber, Morgan L.; Lacika, Julia F.; Thompson, Graham J. (Frontiers in Bee Science, 2024)
The holobiont theory of evolution explains how individuals are deeply symbiotic with their gut microbes, such that microbes are adapted to influence host metabolism, immunity and behaviour, as signalled from the gut to the brain. For eusocial taxa like the Western honey bee (Apis mellifera), this brain-gut axis may scale up from the individual to affect entire colonies. Here, we examine how microbial supplementation of honey bee feeds could manipulate the brain-gut axis to affect hygienic and other social behaviours relevant to beekeeping, such as foraging, recruitment (dance language) and defense. To illustrate this concept, we focus on various lactic acid-producing bacteria that can synthesize neurotransmitters such as octopamine, dopamine, serotonin and γ-aminobutyric acid, which can influence an individual bee's behavioural cycles and responsiveness to environmental cues. If the behaviour of a worker bee can be deliberately manipulated, and this effect multiplied across many workers, microbial neurotherapeutics could conceivably render colonies more behaviourally responsive to symptoms of disease, or more motivated to forage or possibly less aggressive towards beekeepers. Drawing from the scientific literature, we infer how microbial supplements, such as neurostimulatory or neurosuppressive probiotics, could be applied or even engineered to co-opt the brain-gut axis to bolster hive health or improve performance. The mechanistic link between the gut microbiota and the collective social behaviour of hives remains an understudied aspect of honey bee social biology with relevance to apiculture.